PENGAMBILAN KEPUTUSAN DALAM PERILAKU ORGANISASI - Dedek Kusnadi (Universitas Batanghari Jambi, 2015)
Efforts to establish the effectiveness of a leader lies solely on technical skills and debriefing dimensional conceptual skills. The personal skills become marginalized. Though the true effectiveness of managerial activities and their effects on organizational performance, highly dependent on the sensitivity of the leadership to use their personal skills. Personal skills include the ability to understand the behavior of individual and group behavior in the contribution to shaping the dynamics of the organization, the ability to modify behavior, the ability to understand and provide motivation, ability to understand the process of perception and creation of effective communication, the ability to understand the relation between the concept of power-political leadership in organization, the ability to understand the genealogy of conflict and negotiation, and the ability to construct an ideal organizational culture.Keyword : Decision, Organizational Behavior